How Phytohormones Shape Interactions between Plants and the Soil-Borne Fungus Fusarium oxysporum - Di, Xiaotang; Takken, Frank L. W.; Tintor, Nico (Frontiers in Plant Science, 2016)
Plants interact with a huge variety of soil microbes, ranging from pathogenic to mutualistic. The Fusarium oxysporum (Fo) species complex consists of ubiquitous soil inhabiting fungi that can infect and cause disease in over 120 different plant species including tomato, banana, cotton and Arabidopsis. However, in many cases Fo colonization remains symptomless or even has beneficial effects on plant growth and/or stress tolerance. Also in pathogenic interactions a lengthy asymptomatic phase usually precedes disease development. All this indicates a sophisticated and fine-tuned interaction between Fo and its host. The molecular mechanisms underlying this balance are poorly understood. Plant hormone signaling networks emerge as key regulators of plant-microbe interactions in general. In this review we summarize the effects of the major phytohormones on the interaction between Fo and its diverse hosts. Generally, Salicylic Acid (SA) signaling reduces plant susceptibility, whereas Jasmonic Acid (JA), Ethylene (ET), Abscisic Acid (ABA) and auxin have complex effects, and are potentially hijacked by Fo for host manipulation. Finally, we discuss how plant hormones and Fo effectors balance the interaction from beneficial to pathogenic and vice versa.